A clinical perspective on immunoglobulin heavy chain clonal heterogeneity in B cell acute lymphoblastic leukemia. (December 2018) - Fries, Carol; Burack, W. Richard
Highlights: Abundant intra-clonal heterogeneity exists within acute lymphoblastic leukemia. Intra-clonal variation complicates the interpretation of leukemia detection assays. Sequencing-based methods may enhance minimal residual disease detection sensitivity. Abstract: B cell acute lymphoblastic leukemia (B ALL) is a genetically heterogeneous neoplasm often demonstrating extensive subclone diversity within each patient's disease. The immunoglobulin heavy chain ( IGH ) locus is a marker of clonal variation in B ALL due to its intrinsic role in B lymphocyte development and its diverse Vh(D)Jh rearrangement patterns. B ALL IGH evolution may contribute to limitations in minimal residual disease (MRD) monitoring methods. Evolving technologies for IGH high-throughput sequencing (HTS) have demonstrated MRD detection as sensitive as 1 cell in 1, 000, 000. These methods may enhance the surveillance of B ALL in the setting of extensive subclone evolution and provide opportunities for detection and intervention before the onset of relapse. However, HTS MRD methods will need to be evaluated in the context of clinical trials in order to gain further insights about the clinical relevance of such sensitive B ALL MRD detection.